Ответ:
0 и ещё что то
Пошаговое объяснение:
(8 (а^8)^7*а) /((а^11)^3*(а^13)*(а^9))*x=
=(8 (а^56) *а) /((а^33)*(а^13)*(а^9))*х=
=(8 а^(56+1))/(а^(33+13+9))*х=
= (8 а^57)/(а^55)*х=8 а^(57-55)*х=
=8 а^2*х
8а^2 *х=а*(16х+24)
8а^2*х=16*х*а+24а
8а^2*х-16*а*х-24а=0
8а(ах-2х-3)=0
8а=0 ах-2х-3=0
а=0 ох если честно я не знаю как дальше
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
0 и ещё что то
Пошаговое объяснение:
(8 (а^8)^7*а) /((а^11)^3*(а^13)*(а^9))*x=
=(8 (а^56) *а) /((а^33)*(а^13)*(а^9))*х=
=(8 а^(56+1))/(а^(33+13+9))*х=
= (8 а^57)/(а^55)*х=8 а^(57-55)*х=
=8 а^2*х
8а^2 *х=а*(16х+24)
8а^2*х=16*х*а+24а
8а^2*х-16*а*х-24а=0
8а(ах-2х-3)=0
8а=0 ах-2х-3=0
а=0 ох если честно я не знаю как дальше